Prevalenza del tatuaggio e del body piercing e relazione con il corpo in un campione di 485 studenti universitari: risultati preliminari. - Martino, Marina; Cello, Stefania; Iannaccone, Mara; Cotrufo, Paolo (Rivista di Psicologia Clinica, 2013)
Purpose: We conducted a study with the following objectives: 1) to quantify the prevalence of persons who resort to practices of body modifications (BM) in a natural population, 2) to investigate the conscious motivations that drive these people to resort to such practices; 3 ) to detect differences in the relationship with their own bodies between those who practice BM and those who do not practice; 4) to evaluate the possible presence of body image concerns.Method: We administered to a university’s students population the following tools: a socio-demographic form ad hoc scale IM dell’EDI2, the Body Uneasiness Test, the General Health Questionnaire 28. Results: The sample consisted of 485 subjects aged between 18 and 40 years. 15.1% of the subjects reported the presence of tattoos and 21.9% of piercing. The presence of tattoos and/or piercings appears to be correlated with risk behavior. We found in subjects BM greater body image concerns. The main conscious motivation that push this subjects to BM were found to be an expression of yourself and remember. Discussion: The results obtained from our study confirm that even in Italy there is an increase of BM, in accordance with what reported in the literature. It also seems to be present, in those who engage in such practices, a special relationship with their own body.